Digital Storytelling in a Saudi EFL Classroom: An Exploratory Study of its Impact on Students’ Intrinsic Motivation and Willingness to Communicate - Al-Amri, Haifa Mohammed (Curtin University, 2021)
This study was an attempt to help TESOL teachers struggling with their students' reticence in the classroom. It offered a practical, research-informed solution to reduce students' reticence and increase their classroom oral production. The proposed intervention was the integration of digital storytelling pedagogy. Its alignment with the principles of the communicative approach, possession of factors crucial for enhancing willingness to communicate as well as intrinsic motivation made it capable of achieving the overarching goal of reducing language learners' reticence.